Microstructural characterization of TiB2–SiC–BN ceramics prepared by hot pressing. Issue 20 (15th October 2021) - Song, Bin; Yang, Wei; Liu, Xiaoming; Chen, Haiyan; Akhlaghi, Maryam
Abstract: This research intended to evaluate the discrete and cumulative impacts of hexagonal SiC and BN additives on the microstructural features and consolidation behavior of TiB2 -based materials. All specimens were sintered at the same hot-pressing conditions at 2000 °C under 50 MPa for 120 min. Both discrete and synergetic influences of SiC and hBN ingredients on the sintering behavior of TiB2 were noticeable so that three near fully dense ceramics were secured. Due to a chemical interaction between SiC and TiO2 phases, in-situ SiO2 was generated during the hot pressing of the TiB2 –SiC sample. Although no in-situ phase could be detected in the composite introduced by hBN additive, the X-ray diffraction pattern and electron microscopy images uncovered the in-situ generation of the TiC phase in the ternary and binary systems of TiB2 –SiC-hBN and TiB2 –SiC. While both TiB2 –SiC-hBN and TiB2 –SiC samples were mostly fractured intergranularly, a mixed transgranular-intergranular fracture mode was seen in the fracture surface of the TiB2 -hBN ceramic. The finest microstructure was attained when both SiC and hBN additives were incorporated into the TiB2 matrix at the same time. Finally, the sample introduced by 25 vol% SiC reinforcement reached the most significant Vickers hardness (24.3 GPa), while the TiB2 –SiC-hBN composite offered the highest fracture toughness (6.7 MPa m 1/2 ).